Religious factor of social dynamics: semantic aspect - Abysova, М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is devoted to the semantic aspect of the dialectics of sacralization and secularization as an integral part of social changes.